KEHIDUPAN MEMBIARA DAN JEBAKAN TAKDIR: SUBJEKTIVITAS ROMO YB MANGUNWIJAYA DALAM PERSPEKTIF SLAVOJ ŽIŽEK - Taum, Yoseph Yapi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
The monastic life for celibate individuals is not a problem-free life choice. As human beings, individuals who choose the monastic life face various biological, sociological, and psychological upheavals that are not easily overcome. These upheavals can lead to a crisis of faith. This study aims to uncover the issues faced by celibate individuals as depicted in the novel "Romo Rahardi" by YB Mangunwijaya. The study will employ Slavoj Žižek's symbolic discursive theory to unravel the symbolic entanglements that constrain the subjects and reveal the characters' positions in confronting their lives as celibate individuals. This research is a qualitative descriptive study that utilizes a discursive approach. The findings of this research reveal fractures and disorientation in the subjective realm. When Rahadi reaches the age of puberty, he becomes aware of the extraordinary sexual attraction towards the opposite sex, and he views this phenomenon as something good, natural, and positive. However, this awareness becomes a tremendous black hole as Rahadi enters the symbolic order. The celibate lifestyle confines him without the opportunity to explore alternative paths. In the real realm, when Rahadi reflects on the reality of his life as a spiritual person, he discovers a fragmented and incomplete subjective condition that is far from ideal—a primordial and absurd alienation. There exists a homology between Romo Rahadi and Romo YB Mangunwijaya.